Pembelajaran Berdiferensiasi dan Kreativitas Menulis Cerpen Peserta Didik Program Sekolah Penggerak Angkatan Pertama Jenjang SMP Kota Probolinggo - Susanto, Moh. Arif; Sandi, Elita Arcelina; Shofiani, Arisni Kholifatu Amalia (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
This study aims to describe the tendency of creativity in writing short stories for students of the first batch of Probolinggo junior high school program students with the application of differentiated learning. The research method used is descriptive quantitative with data analysis using percentages. The research subjects of the first batch of PSP Junior High School students in Probolinggo City for the 2021/2022 academic year were 60 respondents. Collecting data using a questionnaire in the form of a statement using a Likert scale. Differentiated learning outcomes on students' short story writing creativity are in the very positive category. The results of the analysis of each variable indicator of creativity in writing short stories are in the positive category. Each indicator shows the results of the analysis, namely: 1) Being able to get story ideas from their own experience or from others, the percentage of the result is 77.5%, 2) Being able to arrange a story line according to the structure by pulling the percentage of the result is 75.41% 3) Able to write stories using creative language the result is 71.66%. By using differentiated learning, it is easier for students in the learning process.